Rabban Gamliel and His Dynasty in the Tosefta: Viewing the Nasi through Biblical and Roman Lenses - Wilfand Ben-Shalom, Yael (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2025)
This study examines the portrayal of Rabban Gamliel II (also known as Rabban Gamliel of Yavneh) and his household in the Tosefta. This text includes stories and anecdotes that highlight his unparalleled standing and emphasize the authority of this sage and his dynasty. Some depictions of his lineage draw from Roman frameworks, as suggested by the engagement of Roman imagery of honor, leadership, and patronage. While exploring these depictions, this article also considers the Tosefta’s editorial process and its employment of such narratives. These paired objectives are essential for reassessing the scholarly claim that most passages about Rabban Gamliel and his family (at least those that elevate their status) were later insertions, probably from the third century, intended to legitimize the recently formed patriarchate. Tosefta Shabbat chapter 7, on the "ways of the Amorite," provides a starting point for this two-fold analysis.